Disparity of Consumers and Over-Indebtedness As A Situation of Hypervulnerability for A Re-Reading of Solvency Assessment Policy - Alarcón Cañuta, Miguel Ángel (2024)
The solvency assessment, as a tool for the prevention of consumer over-indebtedness, maintains the paradigm of the average consumer in the way of operating. This paper aims to provide a re-reading of the solvency assessment policy, beyond the paradigm of the average consumer. The argumentative development allows concluding that the finding of the existence of a disparity of types of consumers and the consideration of overindebtedness as a situation of hypervulnerability obliges the designer of the prevention policy to consider a high degree of protection of the consumer´s interests before the risk of economic-financial crisis, and to a solvency evaluation with a holistic perspective and with a differential approach to appreciate the risk of economic-financial crisis and the effects it generates, paying attention to the set of particular and contextual circumstances of the person.